HEALTH DEBATES ON SOCIAL MEDIA: LINKING DIGITAL HEALTH TO COMMUNICATION AND AI STUDIES - Mahnke, Martina Skrubbeltrang; Kjær, Katrine Meldgaard (AoIR Selected Papers of Internet Research, 2020)
Drawing on the examples of three current health debates on Twitter revolving around the hashtags #medicalcannabis, #covid19 and #vaccinationervirker (in English: vaccinations work), this paper explores the broader theoretical question how we may expand the notion of ‘health data’ to include health debates and discussions on social media, and further how these can be linked to concepts of digital health data assemblages and communicative others. By combing insights from AI and communication studies and STS, as well as insights into the human-data relationship from digital health studies, the paper theoretically links digital data assemblages with communication theory which provides tools to think about health data as relational and communicative. With this, social media data becomes relevant in a new light, not only for media scientists, but also for understanding health practices in a digital age more generally. The paper discusses issues this theoretical perspective raises for researchers of social media and online health engagement; what challenges and possibilities this provides in relation to studying social media discussions on health; and finally, an overview of analytical strategies and empirical fields from which these perspectives may be studied.